Original paperTranscatheter implantation of atrial septal occluders in adult patients – evaluation of long-term outcome - Kokocińska, Ewa; Maicka, Agnieszka; Kolińska, Jolanta; D. Kasprzak, Jarosław; Szymczyk, Ewa; Kręcki, Radosław; Figiel, Łukasz; Peruga, Jan Z.; Lipiec, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Background: Transcatheter closure of patent foramen ovale (PFO) and atrial septal defect (ASD) are procedures commonly performed in recent years. Aim : To assess long-term results of percutaneous closure of ASD and PFO in adult patients. Material and methods : The study group comprised 64 patients (45 women, mean age 50.5 ±12.7 years), who in 2004-2010 underwent percutaneous closure of ASD or PFO. The occurrence of clinical end-points in the follow-up and possible changes in quality of life and echocardiographic parameters were taken into consideration. Results : In a mean follow-up period of 310 ±305 days there were no deaths or recurrent neurological or peripheral embolic events. In patients with PFO there was no minimal residual shunt immediately after the procedure in transthoracic and transoesophageal echocardiography, while in patients with ASD early closure of the shunt (up to 24 h) was achieved in 64% of patients, and after 8 months of observation in 84%. The majority of patients were free of complications after the procedure, but one patient underwent urgent surgery after dislocation of the device within 3 h of the procedure and two patients were diagnosed with new-onset atrial fibrillation (AF) about one month after the procedure. Telephone survey revealed that most patients (81% of patients with ASD and 29% of patients with PFO) noted a marked improvement in health status, relief of symptoms of heart failure, syncope and other symptoms experienced prior to the procedure. Conclusions : Transcatheter closure of ASD and PFO is a safe and effective procedure. Moreover, a significant improvement of quality of life can be observed.